Leonid Shemetkov. His entire life devotion - Skiba, A.N.; Monakhov, V.S.; Selkin, M.V.; Vorob’ev, N.T.; Semenchuk, V.N.; Vasil’ev, A.F. (Algebra and Discrete Mathematics, 2013)
It is given a short scientific biography of Professor L.A. Shemetkov.